Effects of aroma and taste, independently or in combination, on appetite sensation and subsequent food intake - Yin, Wenting; Hewson, Louise; Linforth, Rob S.T.; Taylor, Moira A.; Fisk, Ian D. (Elsevier, 2017)
Food flavour is important in appetite control. The effects of aroma and taste, independently or in combination, on appetite sensation and subsequent food intake, were studied. Twenty-six females (24 ± 4 years, 20.9 ± 1.9 kg⋅m-2) consumed, over 15 min period, one of four sample drinks as a preload, followed by an ad libitum consumption of a pasta meal (after 65 min). Sample drinks were: water (S1, 0 kcal), water with strawberry aroma (S2, 0 kcal), water with sucrose and citric acid (S3, 48 kcal) and water with strawberry aroma, sucrose and citric acid (S4, 48 kcal). Appetite sensation did not differ between the S1 (water), S2 (aroma) and S3 (taste) conditions. Compared with S1 (water), S2 (aroma) and S3 (taste), S4 (aroma + taste) suppressed hunger sensation over the 15 min sample drink consumption period (satiation) (p < 0.05). S4 (aroma + taste) further reduced hunger sensation (satiety) more than S1 at 5, 20 and 30 min after the drink was consumed (p < 0.05), more than S2 (aroma) at 5 and 20 min after the drink was consumed (p < 0.05), and more than S3 (taste) at 5 min after the drink was consumed (p < 0.05). Subsequent pasta energy intake did not vary between the sample drink conditions. S4 (aroma + taste) had the strongest perceived flavour. This study suggests that the combination of aroma and taste induced greater satiation and short-term satiety than the independent aroma or taste and water, potentially via increasing the perceived flavour intensity or by enhancing the perceived flavour quality and complexity as a result of aroma-taste cross-modal perception.